Ceramic Electronic Components

A ceramic electronic component with a Ba, Zn, and Si oxide boundary layer and B, Si, and Ba glass frit enhances bonding reliability and thermal shock resistance by mutual diffusion and stress relief, addressing the peeling issue at the electrode interface.

JP7606368B2Active Publication Date: 2024-12-25TDK CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021036612
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-08
Publication Date
2024-12-25
Estimated Expiration
2041-03-08

AI Technical Summary

Technical Problem

Ceramic electronic components face reliability issues due to stress at the interface between baked electrodes and the element body, leading to potential peeling off under thermal shock.

Method used

Incorporating a boundary layer containing Ba, Zn, and Si oxides at the interface between the ceramic layer and external electrode, along with a glass frit composed of B, Si, and Ba, enhances bonding reliability by mutual diffusion and stress relief.

Benefits of technology

The proposed configuration significantly improves the bonding strength and resistance to thermal shock, preventing electrode peeling and ensuring reliable electrical connections.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606368000006
    Figure 0007606368000006
  • Figure 0007606368000007
    Figure 0007606368000007
  • Figure 0007606368000001
    Figure 0007606368000001
Patent Text Reader

Abstract

To provide a ceramic electronic component with a high joint reliability for an element body and an external electrode.SOLUTION: The ceramic electronic component includes: an element body including a ceramic layer and an internal electrode layer; and an external electrode formed in an end surface of the element body, the external electrode being electrically connected to at least a part of the internal electrode layer. The ceramic layer mainly includes a perovskite compound expressed by ABO3. The external electrode includes a conductor and glass frit dispersed in the conductor, and the glass frit contains B, Si, Ba, and Zn. There is an interface layer in an end part of the ceramic layer in contact with the external electrode in an end surface of the element body, and includes an oxide including Ba, Zn, and Si.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a ceramic electronic component having external electrodes. [Background technology]

[0002] As shown in Patent Document 1, a ceramic electronic component is known that includes an element body containing a ceramic component and external electrodes formed on the outer surface of the element body. Baked electrodes are widely used as the external electrodes of ceramic electronic components, and can be formed by applying a conductive paste containing conductor powder and glass frit to the surface of the element body and baking it. Baked electrodes can achieve higher bonding strength than plated electrodes or resin electrodes formed directly on the surface of the element body.

[0003] However, when a ceramic electronic component is subjected to a load such as thermal shock, stress is generated at the interface between the baked electrode and the surface of the element body, which may cause the baked electrode to peel off from the surface of the element body. Therefore, there is a need to develop a technology to improve the reliability of the bond between the element body and the baked electrode. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 4-171912 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in view of the above circumstances, and has an object to provide a ceramic electronic component having high bonding reliability between the element body and external electrodes. [Means for solving the problem]

[0006] In order to achieve the above object, a ceramic electronic component according to the present invention comprises: an element body including a ceramic layer and an internal electrode layer; an external electrode formed on an end surface of the element body and electrically connected to a part of the internal electrode layer; The ceramic layer contains a perovskite-type compound represented by ABO3 as a main component, the external electrodes include a conductor and a glass frit dispersed in the conductor, the glass frit including B, Si, Ba, and Zn; At the end face of the element body, a boundary layer exists at the end of the ceramic layer that contacts the external electrode, and the boundary layer contains an oxide containing Ba, Zn, and Si.

[0007] The inventors have found that the ceramic electronic component having the above-mentioned configuration can improve the bonding reliability between the element body and the external electrodes compared to the conventional case. That is, in the ceramic electronic component of the present invention, peeling of the external electrodes from the end faces of the element body can be suppressed even if the component is subjected to thermal shock. The reason why the above effect is obtained is not necessarily clear, but the following reasons are thought to be the cause.

[0008] First, it is believed that the interdiffusion phenomenon contributes to the improvement of the bonding reliability. In the present invention, Ba, Zn, and Si are common components between the external electrode and the boundary layer. Therefore, it is believed that the common components interdiffuse between the external electrode and the boundary layer, and this interdiffusion improves the bonding strength of the external electrode to the element body. In addition, the boundary layer containing the above-mentioned specific elements is believed to act to relieve the thermal stress generated between the element body and the external electrode, and this stress relaxation action is believed to improve resistance to thermal shock and the like.

[0009] Preferably, the boundary layer further contains the perovskite compound. When the boundary layer contains a main component constituting the ceramic layer of the element body, the bonding strength between the boundary layer and the element body is further improved.

[0010] In the oxide contained in the boundary layer, when the sum of the content of Ba, the content of Zn, and the content of Si is 1 part by mol, preferably, The content of Zn is 0.27 to 0.40 parts by mole, The Si content is 0.27 to 0.40 parts by mole, The remainder is Ba. Alternatively, preferably, the oxide contained in the boundary layer is BaZnSiO4. When the boundary layer satisfies the above requirements, the bonding reliability between the element body and the external electrodes tends to be further improved.

[0011] In the glass frit contained in the external electrode, when the sum of the content of B, the content of Si, the content of Ba, and the content of Zn is taken as 1 part by mol, preferably, The Si content is 0.05 to 0.20 parts by mole, The content of Ba is 0.05 to 0.25 parts by mole, The content of Zn is 0.15 to 0.35 parts by mole, The balance is B. When the external electrodes satisfy the above requirements, the bonding reliability between the element body and the external electrodes tends to be further improved.

[0012] Preferably, the conductor included in the external electrode contains Cu.

[0013] In addition, preferably, in a cross section including the bonding boundary between the end face of the element body and the external electrode, there are three or more diffusion regions in which the glass frit is in direct contact with the boundary layer within 100 μm of the bonding boundary. By satisfying this requirement, the bonding reliability between the element body and the external electrode tends to be further improved. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a cross-sectional view showing a multilayer ceramic capacitor according to one embodiment of the present invention. [Diagram 2] FIG. 2 is an enlarged cross-sectional view of a main portion of a region II shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, the present invention will be described in detail based on the embodiments shown in the drawings.

[0016] In this embodiment, a multilayer ceramic capacitor 2 shown in Fig. 1 will be described as an example of a ceramic electronic component according to the present invention. The multilayer ceramic capacitor 2 has an element body 4 and a pair of external electrodes 6 formed on the outer surface of the element body 4.

[0017] The shape of the element body 4 shown in FIG. 1 is generally a substantially rectangular parallelepiped shape, and has two end faces 4a facing each other in the X-axis direction, two side faces 4b facing each other in the Y-axis direction, and two side faces 4b facing each other in the Z-axis direction. However, the shape of the element body 4 is not particularly limited, and may be an elliptical cylinder, a cylindrical shape, or another prismatic shape. In addition, the outer dimensions of the element body 4 are also not particularly limited, and may be, for example, a length L0 in the X-axis direction of 0.4 mm to 5.7 mm, a width W0 in the Y-axis direction of 0.2 mm to 5.0 mm, and a height T0 in the Z-axis direction of 0.2 mm to 3.0 mm. In this embodiment, the X-axis, Y-axis, and Z-axis are perpendicular to each other.

[0018] The element body 4 has ceramic layers 10 and internal electrode layers 12 that are substantially parallel to a plane including the X-axis and Y-axis, and inside the element body 4, the ceramic layers 10 and the internal electrode layers 12 are alternately stacked along the Z-axis direction. Here, "substantially parallel" means that most parts are parallel, but may have some parts that are not parallel, and the ceramic layers 10 and the internal electrode layers 12 may have some unevenness or be inclined.

[0019] The ceramic layer 10 contains a perovskite compound represented by the general formula ABO3 as a main component. Here, the main component of the ceramic layer 10 refers to a component contained in the ceramic layer 10 at 80 mol % or more based on the entire ceramic layer 10.

[0020] In the perovskite type compound, it is preferable that at least Ba is contained in the A site, and among the perovskite type compounds, in particular, barium titanate (BT) or barium calcium titanate (BCT) is more preferable. Barium titanate and barium calcium titanate are generally represented by the composition formula (Ba 1-a-b Sr a Ca b ) m (Ti 1-c-d Zr c Hf d )O3.

[0021] In the above composition formula, the symbols a, b, c, d, and m each indicate an element ratio, and each element ratio is not particularly limited and can be set to a known range. For example, m indicates the element ratio of the A site to the B site, and can generally be in the range of 0.9 to 1.1. Furthermore, a indicates the element ratio of Sr in the A site, and b indicates the element ratio of Ca in the A site. In this embodiment, it can be 0≦a+b<1, and it is preferable that it is 0≦a+b≦0.1. Furthermore, c indicates the element ratio of Zr in the B site, and d indicates the element ratio of Hf in the B site. In this embodiment, it can be 0≦c+d<1.0, and it is preferable that it is 0≦c+d≦0.15. In addition, the element ratio of oxygen (O) in the above composition formula may be slightly deviated from the stoichiometric composition.

[0022] In addition to the above-mentioned main components, the ceramic layer 10 may contain auxiliary components. Examples of the auxiliary components include Mn compounds, Mg compounds, Cr compounds, Ni compounds, rare earth element compounds, Si compounds, Li compounds, B compounds, and V compounds, and the types, combinations, and amounts of the auxiliary components added are not particularly limited.

[0023] The average thickness Td (interlayer thickness) per layer of the ceramic layers 10 is not particularly limited, and can be, for example, 100 μm or less, and preferably 30 μm or less. The number of layers of the ceramic layers 10 may be determined according to the desired characteristics, and is not particularly limited. For example, it can be 20 layers or more, and more preferably 50 layers or more.

[0024] On the other hand, the internal electrode layers 12 are laminated between the ceramic layers 10, and the number of layers is determined according to the number of layers of the ceramic layers 10. The average thickness Te of each of the internal electrode layers 12 is not particularly limited, and can be, for example, 3.0 μm or less.

[0025] Furthermore, the multiple internal electrode layers 12 are stacked such that one end is alternately exposed on two end faces 4a opposing each other in the X-axis direction of the element body 4. A pair of external electrodes 6 are formed on one end face 4a of the element body 4, and are electrically connected to the exposed ends of the alternately arranged internal electrode layers 12. By forming the external electrodes 6 in this manner, the external electrodes 6 and the internal electrode layers 12 form a capacitor circuit.

[0026] That is, the internal electrode layer 12 serves to apply a voltage to each ceramic layer 10 as a part of the capacitor circuit. Therefore, the material of the internal electrode layer 12 includes a conductive material. Specific examples of the material include Cu, Ni, Ag, Pd, Au, Pt, or an alloy containing at least one of these metal elements. More preferably, the conductive material included in the internal electrode layer 12 is Ni or a Ni-based alloy, since the material of the ceramic layer 10 has reduction resistance. In addition, when Ni or a Ni-based alloy is the main component, one or more types of subcomponents for the internal electrode selected from Mn, Cu, Cr, etc. may be included.

[0027] In addition to the conductive material, the internal electrode layer 12 may contain the ceramic components contained in the ceramic layer 10 as co-materials, and may contain trace amounts (for example, about 0.1 mass % or less) of non-metallic components such as S and P.

[0028] 1, the external electrode 6 of this embodiment integrally has an end surface portion formed on the end surface 4a in the X-axis direction of the element body 4, and extended portions formed at the ends in the X-axis direction on the four side surfaces 4b of the element body 4. That is, the pair of external electrodes 6 are each formed so as to wrap around from the end surface 4a to the side surfaces 4b of the element body 4. The pair of external electrodes 6 are insulated so as not to contact each other in the X-axis direction.

[0029] As described above, in this embodiment, the extensions of the external electrodes 6 are formed on each of the four side surfaces 4b of the element body 4. However, the extensions of the external electrodes 6 are not essential, and the external electrodes 6 may be composed of only the end surface portions. Alternatively, when the multilayer ceramic capacitor 2 is surface-mounted on a substrate, it is sufficient that the extensions of the external electrodes 6 are formed on at least the side surface 4b facing the mounting surface of the substrate, and they do not have to be formed on the side surface 4b opposite the mounting surface.

[0030] Fig. 2 is a schematic cross-sectional view in which a joint boundary 46 between the external electrode 6 and the element body 4 is enlarged. Note that Fig. 2 shows one of a pair of external electrodes 6, but the other external electrode 6 has the same characteristics as those in Fig. 2. Hereinafter, detailed characteristics of the external electrode 6 in this embodiment and the joint state between the external electrode 6 and the element body 4 will be described with reference to Fig. 2.

[0031] As shown in FIG. 2, the external electrode 6 has a baked electrode 6a including a conductor 61 and a glass frit 62, and the baked electrode 6a is in contact with the outer surface (end surface 4a) of the element body 4. The external electrode 6 may be composed of a single electrode layer, or may be composed of a laminate of multiple electrode layers. When the external electrode 6 is composed of multiple electrode layers, the baked electrode is formed so as to be in contact with the outer surface of the element body 4, and another baked electrode, a resin electrode, a plated electrode, or the like is formed on the baked electrode. For example, the external electrode 6 may have a three-layer structure of a baked electrode-Ni plating layer-Sn plating layer (laminate in the order shown). In this case, the Sn plating layer is located on the outermost surface of the external electrode 6, so that the solder wettability of the external electrode 6 is good.

[0032] The average thickness of the fired electrode 6a in contact with the end face 4a may be 5 μm to 200 μm, and is preferably 50 μm or less. When the external electrode 6 is composed of multiple layers, the average thickness of the external electrode 6 may be about 5 μm to 300 μm, and is preferably 100 μm or less.

[0033] The conductor 61 included in the baked electrode 6a is a conductive metal, and may be, for example, Cu, Ni, Ag, Pd, Au, Pt, or an alloy containing at least one of these metal elements, and is preferably Cu or a Cu alloy. When the conductor 61 is a Cu alloy, the conductor 61 may contain elements other than Cu, such as Al, Ni, Ag, Pd, Sn, Zn, P, Fe, and Mn. The amount of elements other than Cu is preferably 5 molar parts or less relative to 100 molar parts of Cu.

[0034] On the other hand, the glass frit 62 is an amorphous glass containing B, Si, Ba, and Zn, and is dispersed in the conductor 61. The composition of the glass frit 62 preferably satisfies the following condition: When the sum of the content of B, the content of Si, the content of Ba, and the content of Zn is 1 part by mol, the content of Si is preferably 0.05 parts by mol to 0.20 parts by mol, the content of Ba is preferably 0.05 parts by mol to 0.25 parts by mol, the content of Zn is preferably 0.15 parts by mol to 0.35 parts by mol, and the remainder is B (preferably the content of B is 0.20 parts by mol to 0.60 parts by mol).

[0035] The compound structure of the glass frit 62 is not particularly limited, and the above composition ratio may be realized by mixing a plurality of glass components. For example, the glass frit 62 may be a mixture of a glass component made of SiO2 and a glass component made of B2O3-BaO-ZnO (preferably Ba3Zn(BO3)2). The glass frit 62 may contain trace elements in addition to the above-mentioned main elements (B, Si, Ba, Zn, O). Examples of the trace elements include Al, rare earth elements, Zr, Mn, Ca, Mg, Ti, K, and Na, and the total content of the trace elements is preferably 0.20 molar parts or less with respect to 1.0 molar part of the total content of the main elements excluding O.

[0036] As described above, the baked electrode 6a includes the conductor 61 and the glass frit 62, and may also include voids and oxide subcomponents (not shown). The content ratio of the conductor 61 to the glass frit 62 in the baked electrode 6a is not particularly limited. For example, the average area ratio of the conductor 61 to the cross section of the baked electrode 6a may be 30% to 90%, and is preferably 70% to 90%.

[0037] The external electrodes 6 can be analyzed by cross-sectional observation using a SEM (scanning electron microscope) or a STEM (scanning transmission electron microscope). For example, the compositions of the conductor 61 and the glass frit 62 can be measured by component analysis using an electron probe microanalyzer (EPMA) during cross-sectional observation. It is preferable to perform component analysis at least at three or more locations and calculate the composition of each element (61, 62) from the average value of the measurement results. In this embodiment, when component analysis is performed using an EPMA, an EDS (energy dispersive spectrometer) or a WDS (wavelength dispersive spectrometer) can be used as the X-ray spectrometer.

[0038] The area ratio of the conductor 61 can be measured by image analysis of a cross-sectional photograph obtained by cross-sectional observation using SEM, STEM, or the like. When the cross-section of the baked electrode 6a is observed using a backscattered electron image of SEM or a HAADF image of STEM, the conductor 61 having a metallic bond can be recognized as a bright contrast area, and non-metallic components such as the glass frit 62 (including voids and oxides) can be recognized as a dark contrast area. Therefore, the area ratio of the conductor 61 in the cross-section of the baked electrode 6a can be calculated as the ratio of the area of ​​the bright contrast area to the area of ​​the entire measurement field by, for example, binarizing the cross-sectional photograph. It is preferable to carry out the measurement in at least five fields of view and calculate the average value.

[0039] 2, a boundary layer 14 is interposed between the external electrode 6 and the ceramic layer 10 of the element body 4. This boundary layer 14 exists at the end of the ceramic layer 10 in the X-axis direction, and constitutes part of the outermost surface of the end face 4a of the element body 4. When the external electrode 6 is formed spanning from the end face 4a to part of the side face 4b, it is preferable that the boundary layer 14 exists not only on the end face 4a but also on the outermost surface of the side face 4b.

[0040] In the cross section shown in FIG. 2, the internal electrode layer 12 penetrates the boundary layer 14 and is exposed at the end face 4a, and the exposed end of the internal electrode layer 12 is electrically connected to the baked electrode 6a (particularly the conductor 61) of the external electrode 6. However, when observing the XZ cross section, there may be a portion at the end face 4a where the boundary layer 14 covers the end (end in the X-axis direction) of some of the internal electrode layers 12. Each internal electrode layer 12 exists along the Y-axis direction, and as long as the end of each internal electrode layer 12 penetrates the boundary layer 14 at least partially and is in direct contact with the baked electrode 6a, even if the end is partially covered by the boundary layer 14, the electrical connection between each internal electrode layer 12 and the external electrode 6 can be ensured. In addition, a part of the external electrode 6 may penetrate into the boundary layer 14, and the joint boundary 46 between the external electrode 6 and the end face 4a (boundary layer 14 or internal electrode layer 12) of the element body 4 may be unclear.

[0041] The average length Lr (average thickness) of the boundary layer 14 in the X-axis direction is preferably 1 μm to 10 μm, and more preferably 3 μm to 8 μm.

[0042] The boundary layer 14 contains, as its main components, oxides including Ba, Zn, Si, and O. The main components of the boundary layer 14 refer to components that are contained in an amount of 50 mol % or more with respect to the entire boundary layer 14. The oxides are preferably non-vitrified crystalline oxides, and specifically, preferably satisfy the following composition.

[0043] That is, in the oxide contained in the boundary layer 14, if the sum of the Ba content, the Zn content, and the Si content (the sum of the contents of the main elements excluding O) is taken as 1 molar part, the Zn content is preferably 0.27 molar parts to 0.40 molar parts, the Si content is preferably 0.27 molar parts to 0.40 molar parts, and the remainder is Ba (preferably, the Ba content is 0.28 molar parts to 0.39 molar parts). Among the oxides satisfying the above composition ratio, it is more preferable that the boundary layer 14 contains BaZnSiO4 in particular.

[0044] Moreover, in addition to the above-mentioned oxides, the boundary layer 14 preferably contains a perovskite compound, which is the main component of the ceramic layer 10. The perovskite compound can be contained in the boundary layer 14 by intentionally adding it to the raw material paste for forming the boundary layer 14. However, it is considered that the perovskite compound diffuses from the ceramic layer 10 and penetrates into the boundary layer 14, and the content of the perovskite compound in the boundary layer 14 is not particularly limited. It is considered that the bonding strength of the boundary layer 14 to the ceramic layer 10 is further improved by containing the main component of the ceramic layer 10 in the boundary layer 14.

[0045] In addition to the above-mentioned oxides and perovskite compounds, the boundary layer 14 may contain trace compounds including Al, Ti, Ca, B, etc. Also, the boundary layer 14 may contain conductive metal components such as Cu and Ni. The contents of the trace compounds and metal components are not particularly limited.

[0046] The boundary layer 14 having the above characteristics has a function of improving the bonding strength between the ceramic layer 10 of the element body 4 and the fired electrode 6a. In particular, a part of the glass frit 62 contained in the fired electrode 6a directly contacts a part of the boundary layer 14, thereby further improving the bonding strength of the fired electrode 6a to the end face 4a. Both the glass frit 62 and the boundary layer 14 contain Ba, Zn, and Si, and it is believed that the bonding strength of the fired electrode 6a is improved by the mutual diffusion of these common elements between the glass frit 62 and the boundary layer 14. In this embodiment, the area where a part of the glass frit 62 directly contacts a part of the boundary layer 14 is referred to as a diffusion region 46a (see FIG. 2).

[0047] It is preferable that a predetermined number or more of the diffusion regions 46a are present within a predetermined length Lz of the joint boundary 46 in the Z-axis direction. Specifically, in a cross section (XZ cross section) including the joint boundary 46 between the end face 4a and the external electrode 6 as shown in Fig. 2, if the predetermined length Lz is 100 µm, it is preferable that three or more diffusion regions 46a are present, and more preferably seven or more diffusion regions 46a are present. There is no particular upper limit on the number of diffusion regions 46a, but from the viewpoint of ensuring electrical connection between the internal electrode layer 12 and the fired electrode 6a, it is preferable that the number be 15 or less.

[0048] In addition, the bond boundary 46 may be meandering or partially unclear in the cross section shown in Fig. 2. When measuring the number of diffusion regions 46a, it is not necessary to accurately measure meandering or unclear parts of the bond boundary 46 to calculate the predetermined length Lz, and the width of the cross section photograph may be regarded as the predetermined length Lz of the bond boundary 46. For example, as shown in Fig. 2, a cross section photograph is taken so that one side of the bond boundary 46 is substantially parallel to the bond boundary 46, and the width of the cross section photograph in the Z-axis direction is regarded as the predetermined length Lz of the bond boundary 46.

[0049] In addition, the particles of the glass frit 62 that are in direct contact with the boundary layer 14 (i.e., the particles of the glass frit 62 that constitute the diffusion region 46a) preferably have a shape that provides an anchor effect. The "particle shape that provides an anchor effect" means that the particles do not spread thinly along the outer surface (YZ plane) of the boundary layer 14, but rather spread three-dimensionally from the outer surface of the boundary layer 14 toward the inside of the baked electrode 6a (i.e., toward the outside in the X-axis direction) as shown in FIG. 2. That is, the particles of the glass frit 62 located at the bond boundary 46 penetrate from the bond boundary 46 toward the gap of the conductor 61, providing an anchor effect like the barb of the hook digging in, and further improving the bond strength of the external electrode 6 to the element body 4. The anchor effect can be achieved, for example, by controlling the particle shape of the glass frit added to the raw material paste of the baked electrode 6a.

[0050] The boundary layer 14 can be analyzed by cross-sectional observation using SEM, STEM, etc., in the same way as the baked electrode 6a. For example, the average length Lr of the boundary layer 14 and the number of diffusion regions 46a can be measured by image analysis of a cross-sectional photograph. The composition of the boundary layer 14 can be measured by component analysis using EPMA.

[0051] Next, an example of a method for manufacturing the multilayer ceramic capacitor 2 shown in FIG. 1 will be described.

[0052] First, a description will be given of the manufacturing process of the element body 4. In the manufacturing process of the element body 4, a dielectric paste that becomes the ceramic layers 10 after firing and an internal electrode paste that becomes the internal electrode layers 12 after firing are prepared.

[0053] The dielectric paste is manufactured, for example, by the following method. First, the dielectric raw material is mixed uniformly by means of wet mixing or the like, and dried. Then, the mixture is heat-treated under predetermined conditions to obtain calcined powder. Next, a known organic vehicle or a known aqueous vehicle is added to the calcined powder obtained and kneaded to prepare a dielectric paste. The dielectric paste thus obtained is formed into a sheet by a method such as a doctor blade method to obtain a ceramic green sheet. The dielectric paste may contain additives selected from various dispersants, plasticizers, dielectrics, auxiliary component compounds, glass frits, etc., as necessary.

[0054] On the other hand, the internal electrode paste is prepared by kneading a conductive powder made of a conductive metal or its alloy with a known binder and solvent. The internal electrode paste may contain a ceramic powder (e.g., barium titanate powder) as a co-material, if necessary. The co-material has the effect of suppressing the sintering of the conductive powder during the firing process.

[0055] Next, the internal electrode paste is applied in a predetermined pattern onto the ceramic green sheets by various printing methods such as screen printing or transfer methods. The green sheets on which the internal electrode patterns are formed are then stacked in multiple layers, and pressed in the stacking direction to obtain a mother laminate. At this time, the ceramic green sheets and the internal electrode patterns are stacked so that the ceramic green sheets are located on the upper and lower surfaces of the mother laminate in the stacking direction.

[0056] The mother laminate obtained by the above process is cut into a predetermined size by dicing or pressing to obtain a plurality of green chips. The green chips may be solidified and dried to remove plasticizers, etc., as necessary, and may be barrel-polished using a horizontal centrifugal barrel machine or the like after solidification and drying. In barrel polishing, the green chips are placed in a barrel container together with media and polishing liquid, and the barrel container is given rotational motion, vibration, etc., to polish away unnecessary parts such as burrs generated during cutting. After barrel polishing, the green chips are washed with a cleaning liquid such as water and dried.

[0057] Next, the green chip obtained above is subjected to a binder removal process and a firing process, and the element body 4 is obtained.

[0058] The conditions for the binder removal treatment are not particularly limited and may be appropriately determined depending on the main component composition of the ceramic layer 10 and the main component composition of the internal electrode layer 12. For example, the temperature increase rate is preferably 5 to 300°C / hour, the holding temperature is preferably 180 to 400°C, and the temperature holding time is preferably 0.5 to 24 hours. The binder removal atmosphere is air or a reducing atmosphere.

[0059] The firing conditions are not particularly limited and may be appropriately determined depending on the main component composition of the ceramic layers 10 and the main component composition of the internal electrode layers 12. For example, the holding temperature during firing is preferably 1200 to 1350°C, more preferably 1220 to 1300°C, and the holding time is preferably 0.5 to 8 hours, more preferably 1 to 3 hours. The firing atmosphere is preferably a reducing atmosphere, and the atmospheric gas may be, for example, a humidified mixed gas of N2 and H2. Furthermore, when the internal electrode layers 12 are made of a base metal such as Ni or a Ni alloy, the oxygen partial pressure in the firing atmosphere may be set to 1.0×10 -14 ~1.0×10 -10 It is preferable that the pressure is set to MPa.

[0060] After the firing process, annealing may be performed as necessary. Annealing is a process for reoxidizing the ceramic layer 10, and it is preferable to perform annealing when the firing process is performed in a reducing atmosphere. The conditions of the annealing process may be appropriately determined according to the main component composition of the ceramic layer 10, and are not particularly limited. For example, the holding temperature is preferably 950 to 1150°C, the temperature holding time is preferably 0 to 20 hours, and the temperature increase rate and temperature decrease rate are preferably 50 to 500°C / hour. In addition, it is preferable to use humidified N2 gas or the like as the atmospheric gas, and the oxygen partial pressure in the annealing atmosphere is 1.0×10 -9 ~1.0×10 -5 It is preferable that the pressure is set to MPa.

[0061] In the above-mentioned binder removal treatment, firing treatment, and annealing treatment, in order to moisten the N2 gas or mixed gas, for example, a wetter or the like may be used, and in this case, the water temperature is preferably about 5 to 75° C. Furthermore, the binder removal treatment, firing treatment, and annealing treatment may be performed consecutively or independently.

[0062] Next, a paste for the boundary layer is applied to the outer surface of the element body 4 obtained above, and then baked to form the boundary layer 14. Note that the boundary layer 14 may be formed by ceramic coating using various vapor deposition methods without using a paste.

[0063] When the boundary layer 14 is formed by a paste, the paste for the boundary layer contains a raw material powder for the boundary layer, a binder, and a solvent, and may also contain a dispersant, a plasticizer, etc., as necessary. As the raw material powder for the boundary layer, a mixed powder of ZnO powder, SiO2 powder, and BaCO3 powder can be used. Alternatively, a powder obtained by mixing ZnO powder, SiO2 powder, and BaCO3 powder in a predetermined ratio, calcining, and pulverizing the mixture can be used. Also, a powder of a complex oxide such as BaZnSiO4 powder can be used as the raw material powder for the boundary layer. In addition to the above, the raw material powder for the boundary layer may contain a powder of a dielectric compound that is the main component of the ceramic layer 10, a powder of a trace compound such as Al2O3, a Cu powder, Ni powder, or an alloy powder containing Cu, Ni, etc.

[0064] The binder, solvent, and dispersant used in the boundary layer paste are not particularly limited and may be the same as those used in the dielectric paste. For example, the binder may be appropriately selected from various common binders such as ethyl cellulose, acrylic, butyral, and the solvent may be appropriately selected from various organic solvents and aqueous solvents such as terpineol, butyl carbitol, alcohol, methyl ethyl ketone, acetone, and toluene.

[0065] The boundary layer paste can be applied to the element body 4 by a dipping method, various printing methods such as screen printing, application methods using a dispenser, spraying methods using a spray, etc. The boundary layer paste is applied to at least the end face 4a of the element body 4, and may also be applied to a part of the side face 4b on which the external electrode 6 is formed. In this case, the average length Lr (average thickness) of the boundary layer 14 can be adjusted by controlling the amount of the boundary layer paste applied.

[0066] Next, the element body 4 coated with the boundary layer paste is dried and baked at a temperature of 700°C to 1000°C for 0.1 to 3 hours to form the boundary layer 14. The average length Lr of the boundary layer 14 is also affected by the baking conditions. If the temperature during the baking process is set low or the holding time is shortened, the average length Lr tends to become smaller (the average thickness becomes thinner).

[0067] After forming the boundary layer 14, it is preferable to perform a surface treatment such as sandblasting, laser irradiation, barrel polishing, etc. on the end face 4a of the element body 4. By performing such a surface treatment, the end of the internal electrode layer 12 is easily exposed on the outermost surface of the end face 4a, and the electrical connection of the internal electrode layer 12 to the external electrode 6 is improved.

[0068] After the boundary layer 14 is formed, the conductive paste for the baked electrode 6a is applied to the end face 4a of the element body 4, or to the end face 4a and a part of the side face 4b by a dipping method, a printing method, or the like. The conductive paste used in this case contains conductive metal particles that become the conductor 61 after the baking process and glass frit 62, and may also contain other appropriate subcomponent raw materials such as binders, solvents, dispersants, plasticizers, and oxide powders. The number of diffusion regions 46a is influenced by the amount of glass frit 62 added in the conductive paste, and the number of diffusion regions 46a tends to increase as the amount of glass frit 62 added increases.

[0069] Thereafter, the element body 4 coated with the conductive paste is held at a temperature of 700° C. to 1000° C. for 0.1 to 3 hours, thereby forming the baked electrodes 6a.

[0070] When a plated electrode layer is formed on the baked electrode 6a, the element body 4 after the baked electrode 6a is formed may be subjected to a plating process such as electrolytic plating or electroless plating. When a resin electrode is formed on the baked electrode 6a, a conductive paste for resin electrodes containing a thermosetting resin may be applied to cover the baked electrode 6a by a dipping method, a printing method, or the like, and then a hardening process may be performed. In this case, a plated electrode layer may be further formed on the resin electrode. Another baked electrode may be laminated on the baked electrode 6a, and in this case, the baked electrode 6a and the other baked electrode may be baked at the same time.

[0071] Through the above steps, a multilayer ceramic capacitor 2 having external electrodes 6 is obtained.

[0072] In the manufacturing process described above, the boundary layer 14 is formed after the green chip is fired. However, it is also possible to apply a boundary layer paste to the green chip before firing and bake the boundary layer 14 at the same time as firing the green chip.

[0073] In addition, when the boundary layer 14 is formed after the firing of the element body 4, it is preferable to perform a surface treatment such as sandblasting, laser irradiation, barrel polishing, etc., on the element body 4 as a pretreatment. In this case, the end of the ceramic layer 10 is selectively polished rather than the end of the internal electrode layer 12 on the end face 4a of the element body 4 by the surface treatment. Therefore, when the boundary layer paste is applied after the surface treatment, the boundary layer paste is applied to the portion from which the ceramic layer 10 has been selectively removed, and the end of the internal electrode layer 12 is easily exposed to the end face 4a without being covered by the boundary layer 14. As a result, the electrical connection between the end of the internal electrode layer 12 and the external electrode 6 is improved. In addition, the boundary layer paste is applied to the portion from which the ceramic layer 10 has been selectively removed, thereby further improving the bonding strength of the boundary layer 14 to the ceramic layer 10.

[0074] The obtained multilayer ceramic capacitor 2 can be surface-mounted on a substrate such as a printed wiring board using solder (including molten solder, solder cream, and solder paste) or a conductive adhesive, and used in various electronic devices, etc. Alternatively, the multilayer ceramic capacitor 2 can be mounted on a substrate via a wire-shaped lead terminal or a plate-shaped metal terminal.

[0075] (Summary of the embodiment) In the multilayer ceramic capacitor 2 according to this embodiment, the ceramic layers 10 of the element body 4 contain a perovskite compound (such as BT or BCT) as a main component, and the external electrodes 6 (fired electrodes 6a) are composed of a conductor 61 and a glass frit 62 containing B, Si, Ba, and Zn. A boundary layer 14 exists at the end in the X-axis direction of the ceramic layers 10 that contacts the external electrodes 6 (fired electrodes 6a), and the boundary layer 14 contains an oxide containing Ba, Zn, and Si.

[0076] The present inventors have found that the multilayer ceramic capacitor 2 having the above-mentioned configuration improves the reliability of the joint between the element body 4 and the external electrodes 6. That is, the multilayer ceramic capacitor 2 of this embodiment can prevent the external electrodes 6 from peeling off from the end faces 4a of the element body 4 even when subjected to thermal shock. The reason why this effect is obtained is not necessarily clear, but the following reasons are thought to be the cause.

[0077] First, it is believed that the interdiffusion phenomenon contributes to the improvement of the bonding reliability. If the boundary layer 14 does not exist, the common element between the element body 4 and the external electrode 6 is only Ba. On the other hand, in the multilayer ceramic capacitor 2 of this embodiment, the boundary layer 14 is interposed in the bonding portion with the external electrode 6, so that Ba, Zn, and Si become the common elements between the element body 4 and the external electrode 6. In this way, it is believed that the existence of multiple common elements causes multiple common elements to interdiffuse between the fired electrode 6a and the boundary layer 14. As a result, the bonding strength of the external electrode 6 to the element body 4 is improved.

[0078] In particular, it is considered that the more points at which the glass frit 62 of the fired electrode 6a is in direct contact with the boundary layer 14, the more active the interdiffusion becomes. In this embodiment, the number of diffusion regions 46a present within the predetermined length Lz (Lz=100 μm) of the bond boundary 46 is three or more. By satisfying this requirement, the bond strength of the external electrode 6 to the element body 4 is further improved.

[0079] Furthermore, the boundary layer 14 is believed to act to relieve the thermal stress occurring between the element body 4 and the external electrodes 6, and this stress relief effect is believed to improve resistance to thermal shock and the like.

[0080] If the boundary layer 14 does not exist, there is a difference in linear expansion coefficient between the baked electrode containing the amorphous glass frit and the crystalline ceramic layer. In this case, when a thermal shock is applied to the multilayer ceramic capacitor, thermal stress occurs between the baked electrode and the ceramic layer, which is considered to be a factor in the peeling of the baked electrode. On the other hand, in this embodiment, the boundary layer 14 is made of an oxide containing a predetermined element, so that the difference in linear expansion coefficient between the external electrode 6 and the element body 4 is small. That is, the linear expansion coefficient of the boundary layer 14 is close to the linear expansion coefficient of the ceramic layer 10. It is considered that this can suppress the occurrence of thermal stress based on the difference in linear expansion coefficient, and the resistance to thermal shock is further improved.

[0081] In particular, in this embodiment, the main component (oxide) of the boundary layer 14 contains 0.27 to 0.40 molar parts of Zn, 0.27 to 0.40 molar parts of Si, and the remainder is Ba. Alternatively, the main component (oxide) of the boundary layer 14 is BaZnSiO4. When the composition of the boundary layer 14 satisfies the above requirements, it is believed that the difference in linear expansion coefficient between the baked electrode 6a and the end face 4a of the element body 4 becomes smaller, and resistance to thermal shock is further improved. In addition, it is believed that interdiffusion between the baked electrode 6a and the boundary layer 14 becomes more active, and the bonding strength of the external electrode 6 to the element body 4 is further improved.

[0082] Additionally, in this embodiment, the glass frit 62 contained in the fired electrode 6a has a Si content of 0.05 to 0.20 molar parts, a Ba content of 0.05 to 0.25 molar parts, a Zn content of 0.15 to 0.35 molar parts, and the remainder is B. When the composition of the glass frit 62 satisfies the above requirements, it is considered that interdiffusion between the fired electrode 6a and the boundary layer 14 becomes more active, and the bonding strength of the external electrode 6 to the element body 4 is further improved.

[0083] Although an embodiment of the present invention has been described above, the present invention is not limited to the above-described embodiment, and various modifications can be made without departing from the spirit of the present invention.

[0084] For example, in this embodiment, the multilayer ceramic capacitor 2 is exemplified as the ceramic electronic component, but the ceramic electronic component of the present invention may be, for example, a bandpass filter, a multilayer three-terminal filter, a piezoelectric element, a PTC thermistor, an NTC thermistor, a varistor, or the like.

[0085] In this embodiment, the ceramic layers 10 and the internal electrode layers 12 are laminated in the Z-axis direction, but the lamination direction may be the X-axis direction or the Y-axis direction. In this case, the external electrode 6 may be formed in accordance with the exposed surface of the internal electrode layer 12. The element body 4 does not necessarily have to be a laminate, and may be a single layer. Furthermore, the internal electrode layer 12 may be drawn to the outer surface of the element body 4 via a through-hole electrode, in which case the through-hole electrode and the external electrode 6 are electrically connected. EXAMPLES

[0086] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0087] (Experiment 1) In experiment 1, multilayer ceramic capacitors 2 according to Examples 1 to 3 were fabricated according to the following procedure. First, a dielectric paste and an internal electrode paste were prepared, and green chips were fabricated by a sheet method using these pastes. In this case, as the dielectric material that is the main component of the ceramic layers 10, barium titanate (BT) was used in Examples 1 and 2, and barium calcium titanate (BCT) was used in Example 3. In each of the Examples, MgCO3, MnCO3, Y2O3, SiO2, etc. were added as subcomponents of the ceramic layers 10, and Ni was used as the main component of the internal electrode layers 12.

[0088] Next, the green chip obtained above was subjected to a binder removal process under the conditions described in the embodiment, and then the boundary layer paste was applied to the outer surface (end surface) of the green chip by a dipping method and dried. Note that BaZnSiO4 powder was added to all of the boundary layer pastes used in Examples 1 to 3 as the main component of the boundary layer 14. In addition to BaZnSiO4 powder, BaTiO3 powder was added to the boundary layer paste of Example 2, and (Ba,Ca)TiO3 powder was added to the boundary layer paste of Example 3.

[0089] Next, the green chip coated with the boundary layer paste was subjected to a firing process to obtain an element body 4 having a boundary layer 14 formed on the end face 4a. The firing process conditions were a holding temperature of 1250°C, a holding time of 2 hours, and atmospheric gas of humidified N2+H2 mixed gas. Thereafter, the element body 4 was subjected to an annealing process under the conditions described in the embodiment. In addition, the element body 4 was subjected to barrel polishing to expose the ends of the internal electrode layers 12 on the end faces 4a.

[0090] Next, a conductive paste for a baked electrode was prepared, and the conductive paste was applied to the outer surface (end surface 4a and part of the side surface 4b) of the element body 4 by a dipping method, and then dried. In all of the conductive pastes used in Examples 1 to 3, Cu was added as a conductor powder, and B, Si, Ba, and Zn-based glass frits were added as the glass frit 62. Thereafter, the element body 4 to which the conductive paste was applied was held at 800°C for 0.5 hours to bake the conductive paste, and the baked electrode 6a was formed on the outer surface of the element body 4. In addition, a Ni-plated electrode layer and a Sn-plated electrode layer were formed on the baked electrode 6a. In this way, a capacitor sample (multilayer ceramic capacitor 2) on which an external electrode 6 was formed was obtained. Note that more than 400 capacitor samples were manufactured for each of Examples 1 to 3.

[0091] In each of Examples 1 to 3 of Experiment 1, the dimensions of the element body 4 of the capacitor sample were L0×W0×T0=2.0 mm×1.25 mm×1.25 mm. The number of laminated ceramic layers 10 sandwiched between the internal electrode layers 12 was 80.

[0092] In addition, samples for destructive testing were extracted from the capacitor samples according to each of Examples 1 to 3, and cross-sectional observation was performed using the samples by SEM. Specifically, the extracted samples were cut along the XZ plane, and the cross-sections were mirror-polished, after which the average thickness Td of the ceramic layers 10, the average thickness Te of the internal electrode layers 12, the average length Lr of the boundary layers 14, and the average thickness of the fired electrode layers were measured by SEM. The measurement results for Examples 1 to 3 were all as follows.

[0093] Average thickness Td of ceramic layer 10: 10 μm Average thickness Te of the internal electrode layer 12: 1.5 μm Average length of boundary layer 14 Lr: 5 μm Average thickness of baked electrode layer: 25μm

[0094] In addition, in the above cross-sectional observation, the components of the boundary layer 14 and the baked electrode 6a were analyzed by EPMA. As a result, it was confirmed that in all examples, the composition of the raw material powder added to the raw material paste (boundary layer paste and baked electrode conductive paste) and the measurement results were generally consistent. In addition, in the cross-sectional observation, it was confirmed that the boundary layer 14 was formed at the end of the ceramic layer 10 in the X-axis direction in all examples.

[0095] In experiment 1, two types of thermal shock tests (cooling and heating cycle tests) were carried out to evaluate the bonding reliability of the external electrodes 6 in the produced capacitor samples. The details are described below.

[0096] Air tank thermal shock test In the air-bath thermal shock test, the test sample (capacitor sample) was held in an air bath at -55°C for 30 minutes, then held in an air bath at 150°C for 30 minutes, and this was repeated 1000 times. In this test, the pass / fail was judged based on the capacitance decay rate, and the capacitance C before the test was α After the test, the capacitance C β The ratio of (C β / C α ) was rated as passing when it was 0.9 (90%) or more, and as failing when it was less than 0.9. In experiment 1, the above test was carried out on 80 samples for each example, and the ratio of failing samples (NG ratio) was calculated. The evaluation results are shown in Table 1.

[0097] Liquid bath thermal shock test In the liquid bath type thermal shock test, the thermal cycle is performed in a liquid bath instead of an air bath. When using a liquid bath, the test sample is subjected to a steeper temperature change than when using an air bath, so the bonding reliability of the test sample can be evaluated under more severe conditions than in the air bath type test. Specifically, in this embodiment, the test sample was held in a liquid bath at -55°C for 30 minutes per cycle, and then held in a liquid bath at 150°C for 30 minutes, and this was repeated for 1000 cycles. The pass / fail of the liquid bath type thermal shock test was determined based on the capacitance decay rate, as in the air bath type thermal shock test. In experiment 1, the above test was performed on 80 samples for each embodiment, and the ratio of samples that failed (NG ratio) was calculated. The evaluation results are shown in Table 1.

[0098] Comparative Example 1 In Experiment 1, in order to confirm the superiority of Examples 1 to 3 in which the boundary layer 14 is formed, a capacitor sample (multilayer ceramic capacitor) according to Comparative Example 1 in which no boundary layer is formed was manufactured. Specifically, in Comparative Example 1, no boundary layer paste was used, and external electrodes were formed directly on the outer surface of the element body 4 after firing. In Comparative Example 1, the manufacturing conditions were the same as those of Example 1 described above, except that the boundary layer 14 was not formed, and Comparative Example 1 was evaluated in the same manner as Example 1. The evaluation results are shown in Table 1.

[0099] [Table 1]

[0100] As shown in Table 1, in Comparative Example 1, the NG ratio in the air-tank thermal shock test was 5 / 80. On the other hand, in Examples 1 to 3 in which the boundary layer 14 containing a predetermined component was formed, the NG ratio in the air-tank thermal shock test was 0 / 80, confirming that the formation of the boundary layer 14 improves the bonding reliability of the external electrode 6.

[0101] Moreover, the NG ratio in the liquid bath thermal shock test was 0 / 80 in Examples 2 and 3. From this result, it was confirmed that the bonding reliability of the external electrode 6 is further improved by including the main component of the ceramic layer 10 in the boundary layer 14.

[0102] (Experiment 2) In experiment 2, capacitor samples according to Examples 4 to 6 were manufactured by changing the method of forming boundary layer 14. The method of forming boundary layer 14 in each Example will be described below.

[0103] Example 4 In Example 4, similarly to Example 1 of Experiment 1, the boundary layer paste was applied to the green chip before firing, and the boundary layer paste was baked simultaneously with firing the green chip to form the boundary layer 14. In this example, the above formation method is referred to as Manufacturing Method 1. The manufacturing conditions of Example 4 were the same as those of Example 1.

[0104] Example 5 In Example 5, a boundary layer paste was applied by dipping to the outer surface of the element body 4 after the firing and annealing treatment, and then dried. Thereafter, the element body 4 to which the boundary layer paste was applied was baked by holding it at 800°C for 0.5 hours to form the boundary layer 14. In this example, the above-mentioned formation method is referred to as Manufacturing Method 2. The manufacturing conditions of Example 5 other than the above were the same as those of Example 1.

[0105] Example 6 In Example 6, before forming the boundary layer 14, the element body 4 after the firing-annealing treatment was subjected to barrel polishing. Then, a boundary layer paste was applied to the outer surface of the element body 4 after the wet barrel polishing by a dipping method, and dried. Thereafter, the element body 4 to which the boundary layer paste was applied was baked by holding it at 800°C for 0.5 hours, thereby forming the boundary layer 14. In this example, the above-mentioned formation method is referred to as Manufacturing Method 3. The manufacturing conditions of Example 6 other than the above were the same as those of Example 1.

[0106] In Experiment 2, the capacitor samples of Examples 4 to 6 were subjected to a thermal shock test in the same manner as in Experiment 1. In addition, in Experiment 2, a liquid bath type thermal shock test was also performed by increasing the number of evaluation samples (n number) from 80 to 200. The evaluation results are shown in Table 2.

[0107] [Table 2]

[0108] As shown in Table 2, it was confirmed that the bonding reliability of the external electrodes 6 was improved more in Examples 5 and 6 in which the boundary layer paste was applied to the fired element body 4 than in Example 4 in which the boundary layer paste was applied to the green chip. Furthermore, in Example 6, the NG ratio was 0 / 200 even in the liquid bath thermal shock test in which the n number was increased. From this result, it was found that the bonding reliability of the external electrodes 6 was improved more by performing barrel polishing as a pretreatment when forming the boundary layer 14.

[0109] (Experiment 3) In experiment 3, capacitor samples according to Examples 11 to 14 in which the composition ratio of boundary layer 14 was changed, and capacitor samples according to Examples 15 to 20 in which the composition ratio of glass frit 62 was changed were manufactured.

[0110] Specifically, in Examples 11 to 14, BaCO3 powder, ZnO powder, and SiO2 powder were mixed in a predetermined ratio, and then the mixed powder was calcined and pulverized to prepare a raw material powder for the boundary layer paste. Then, using this boundary layer paste, the boundary layer 14 was formed by the same method (manufacturing method 1) as in Example 1 to obtain a capacitor sample. The other experimental conditions in Examples 11 to 14 were the same as in Example 1, and the same evaluations were performed as in Experiment 1. The evaluation results are shown in Table 3. The composition of the boundary layer 14 shown in Table 3 is the measurement result of component analysis using SEM-EPMA, and the content of each element is shown with the total of the Ba content, Zn content, and Si content set to 1.0 part by mole.

[0111] On the other hand, in Examples 15 to 20, the boundary layer 14 was formed by the same method (manufacturing method 1) as in Example 1, and a conductive paste containing glass frit 62 prepared to a predetermined composition ratio was applied onto the boundary layer 14. Here, the glass frit 62 added to the conductive paste was obtained by mixing BaCO3 powder, ZnO powder, SiO2 powder, and B2O3 powder in a predetermined ratio, followed by calcination and pulverization. The conductive paste was applied by a dip method, and then baked to obtain a capacitor sample having a baked electrode 6a. The other experimental conditions in Examples 15 to 20 were the same as in Example 1, and the same evaluations were performed as in Experiment 1. The evaluation results are shown in Table 4. The composition of the glass frit 62 shown in Table 4 is the measurement result of component analysis by SEM-EPMA, and the content of each element is shown with the total of the Ba content, the Zn content, the Si content, and the B content being 1.0 molar part.

[0112] [Table 3]

[0113] [Table 4]

[0114] As shown in Table 3, the NG ratios in both the air bath thermal shock test and the liquid bath thermal shock test were 0% in Examples 11 to 14. This result shows that when the composition of boundary layer 14 is within the range of Examples 11 to 14, the bonding reliability of external electrode 6 can be further improved.

[0115] As shown in Table 4, the NG ratios in both the air bath thermal shock test and the liquid bath thermal shock test were 0% in Examples 15 to 20. This result shows that when the composition of the glass frit 62 is within the range of Examples 15 to 20, the bonding reliability of the external electrode 6 can be further improved.

[0116] (Experiment 4) In experiment 4, capacitor samples according to Examples 21 to 23 were manufactured in which the number of diffusion regions 46a was changed. The number of diffusion regions 46a was controlled by the content of glass frit 62 added to the conductive paste for the fired electrodes. Other than the above, the experimental conditions in Examples 21 to 23 were the same as in Example 1 (i.e., the method for forming the boundary layer 14 was Manufacturing Method 1), and evaluations were performed in the same manner as in Experiment 1. The evaluation results are shown in Table 5.

[0117] The number of diffusion regions 46a was calculated as an average value by extracting five samples for destructive testing from the plurality of manufactured capacitor samples and observing the cross sections of the extracted samples in at least five fields of view.

[0118] [Table 5]

[0119] From the results in Table 5, it was confirmed that when the number of diffusion regions 46a present within 100 μm of the joint boundary is three or more, the joint reliability of the external electrode 6 is further improved. [Explanation of symbols]

[0120] 2. Multilayer ceramic capacitors 4 … Element body 4a … End face 4b…side 10 … Ceramic layer 12 … Internal electrode layer 14 … boundary layer 6 … External electrode 6a … Baked electrode 61 ... Conductor 62 ... Glass frit 46 … Junction boundary 46a … Diffusion area

Claims

1. an element body including a ceramic layer and an internal electrode layer; an external electrode formed on an end surface of the element body and electrically connected to a part of the internal electrode layer; The ceramic layer is made of ABO 3 The perovskite-type compound represented by the formula (I) is contained as a main component. the external electrode includes a conductor and a glass frit dispersed in the conductor; The glass frit contains B, Si, Ba, and Zn, a boundary layer is present at an end of the ceramic layer in contact with the external electrode at an end surface of the element body, and the boundary layer contains an oxide containing Ba, Zn, and Si; The average thickness of the boundary layer is 1 to 10 μm, In a cross section including the boundary layer, A diffusion region where the glass frit particles are in direct contact with the boundary layer has a particle shape that has an anchor effect on the conductor, and the anchor-shaped diffusion region is present at three or more locations within 100 μm of the joint boundary between the boundary layer and the external electrode. Ceramic electronic components.

2. 2. The ceramic electronic component according to claim 1, wherein the boundary layer further contains the perovskite compound.

3. In the oxide contained in the boundary layer, When the sum of the Ba content, the Zn content, and the Si content is 1 part by mol, The content of Zn is 0.27 to 0.40 parts by mole, The content of Si is 0.27 to 0.40 parts by mole, 3. The ceramic electronic component according to claim 1, wherein the balance is Ba.

4. The oxide contained in the boundary layer is BaZnSiO 4 The ceramic electronic component according to any one of claims 1 to 3, wherein

5. In the glass frit contained in the external electrode, When the sum of the B content, the Si content, the Ba content, and the Zn content is 1 part by mol, The content of Si is 0.05 to 0.20 parts by mole, The content of Ba is 0.05 to 0.25 parts by mole, The content of Zn is 0.15 to 0.35 parts by mole, The ceramic electronic component according to any one of claims 1 to 4, wherein the remainder is B.

6. The ceramic electronic component according to any one of claims 1 to 5, wherein the conductor included in the external electrodes contains Cu.

Citation Information

Patent Citations

  • Ceramic capacitor

    JP1992171912A

  • Multilayer ceramic capacitor

    JP2012059742A

  • Multilayer ceramic electronic component and method of manufacturing the same

    JP2017028253A